Behavioral and Metabolic Phenotype Indicate Personality in Zebrafish (Danio rerio) - Yuan, Mingzhe; Chen, Yan; Huang, Yingying; Lu, Weiqun (Frontiers in Physiology, 2018)
Consistency of individual differences of animal behavior and personality in reactions to various environmental stresses among their life stages could reflect basic divergences in coping style which may affect survival, social rank and reproductive success in the wild. However, the physiological mechanisms determining personality remain poorly understood. In order to study whether behavior, metabolism and physiological stress responses relate to the personality, we employed post-stress recovery assays to separate zebrafish into two behavioral types (proactive and reactive). The results demonstrated consistent difference among personality, behavior and metabolism in which proactive individuals were more aggressive, had higher standard metabolic rates and showed lower shuttled frequencies between dark and light compartments than the reactive ones. The behavioral variations were also linked to divergent acute salinity stress responses: proactive individuals adopted a swift locomotion behavior in response to acute salinity challenge while reactive individuals remain unchanged. Our results provide useful insight into how personality acts on correlated traits and the importance of a holistic approach to understanding the mechanisms driving persistent inter-individual differences.